Abnormal skin in toe webs is a marker for abnormal glucose metabolism. A cross-sectional survey among 1,849 adults in Finland - Sinikumpu, Suvi-Päivikki; Auvinen, Juha; Jokelainen, Jari; Huilaja, Laura; Puukka, Katri; Ruokonen, Aimo; Keinänen-Kiukaanniemi, Sirkka; Tasanen, Kaisa; Timonen, Markku (Scientific reports, 2017)
Diabetes is undiagnosed disease and easy screening tools for it are warranted. Because foot complications are usual in diabetes, we aimed to test hypothesis that skin abnormalities are found already from patients who are not aware of having diabetes, by studying the possible association between unhealthy toe web skin and abnormal glucose metabolism. 1,849 cases without previously diagnosed diabetes participated to the 46-year follow-up study of the Northern Finland Birth Cohort. A skin investigation was performed for all, and abnormal skin findings in toe web spaces were taken as explanatory variables. Abnormal glucose tolerance was the main outcome and it was tested with an oral glucose tolerance test (OGTT), glycosylated haemoglobin fraction (HbA 1c ) Values are numbers (percentages) of sub and fasting blood glucose. The participants who had any abnormal skin findings in toe webs were associated with 2.5-fold (OR 2.5, 95% CI 1.3–4.9) and 6-fold (OR 6.2, 1.4–27.6) increased risk of having previously undiagnosed diabetes detected by a 2-hour OGTT and HbA 1c , respectively. The predictive power of toe web findings was comparable with FINDRISC score. Abnormal skin findings in the toe webs show increased risk of occult diabetes, and may, thus serve as an additional sign of undiagnosed diabetes.